Vibronic Dynamics of Photodissociating ICN from Simulations of Ultrafast X‐Ray Absorption Spectroscopy - Morzan, Uriel N.; Videla, Pablo E.; Soley, Micheline B.; Nibbering, Erik T. J.; Batista, Victor S. (Angewandte Chemie International Edition, 2020)
Ultrafast UV‐pump/soft‐X‐ray‐probe spectroscopy is a subject of great interest since it can provide detailed information about dynamical photochemical processes with ultrafast resolution and atomic specificity. Here, we focus on the photodissociation of ICN in the 1Π1 excited state, with emphasis on the transient response in the soft‐X‐ray spectral region as described by the ab initio spectral lineshape averaged over the nuclear wavepacket probability density. We find that the carbon K‐edge spectral region reveals a rich transient response that provides direct insights into the dynamics of frontier orbitals during the I−CN bond cleavage process. The simulated UV‐pump/soft‐X‐ray‐probe spectra exhibit detailed dynamical information, including a time‐domain signature for coherent vibration associated with the photogenerated CN fragment. Ultrafast UV‐pump/soft‐X‐ray‐probe spectroscopy provides detailed information about dynamical photochemical processes with ultrafast resolution and atomic specificity. Here, the photodissociation of ICN in the 1Π1 excited state is studied. The carbon K‐edge spectral region reveals a rich transient response that provides direct insights into the dynamics of frontier orbitals during the I−CN bond cleavage process.